Factors Destabilising the System of Polish Local Government Finances Based on the Example of the City of Kraków in 2018–2023 - Piszczek, Marzena (Journal of Public Governance, 2024)
Objective: The goal of the paper is to characterise the factors destabilising the financial system of Polish local governments in the years 2018–2023 based on the example of the city of Kraków.Research Design & Methods: To achieve the goal, the research used the analysis of law as well as the analysis of the major financial categories such as total incomes, debt, and operational surplus. These factors which had the major impact on destabilising the financial situation of Polish local governments were divided into those dependent on decision-makers (such as the size of subsidies provided for tasks or the tax policy pursued by the Polish government in recent years) and independent ones (including the effects of the COVID-19 pandemic and the war on Poland's eastern border, or an increase of energy and services prices).Findings: Tax policy in particular had a significant impact on the condition of Polish local governments, causing significant revenue losses. The case of the city of Kraków proves this. All of the above-mentioned factors impacted local budgets and resulted in an increase in current budget expenses as well as limited investment opportunities of local government units.Implications / Recommendations: In order to strengthen the financial position of local government, some systemic reforms dedicated to the tax policy and compensatory subsidy must be applied.Contribution / Value Added: Some particular recommendations were proposed. Among them is the legitimacy of continuing works on changes to the self-government financing system. This should result in making the revenue base of territorial self-government units independent of decisions of central authorities as well as in strengthening the area of local taxes. The recommendation also relates to the compensation system and the objectivisation of the principles of allocating targeted subsidies.Article classification: research articleJEL classification: H71, H72, H77